Formulation and in-vitro evaluation of gastroretentive microballoons of riboflavin - Mahejabeen Syeda; Shahnaz Shaik (International Journal of Pharmacy and Analytical Research, 2016)
The present study involves the preparation and evaluation of floating microballoons of riboflavin that has narrow absorption window in the upper part of small intestine. By retaining the dosage form in the stomach and controlling the rate of release prior to reaching the absorption window, free drug can be continuously supplied to its absorption site in the GIT. Microballoons of riboflavin were formulated by emulsion solvent diffusion method employing hydroxy propyl methyl cellulose (HPMC K4M) and ethyl cellulose (EC) polymers and characterized for floating behaviour, in-vitro drug release study, surface morphology using scanning electron microscopy, FT -IR, and differential scanning calorimetry (DSC). FT-IR and DSC studies confirmed the absence of interaction among the drug and polymers. Scanning electron microscopy showed that the microballoons were smooth and almost spherical with free flowing characteristics. Optical microscopic studies revealed the average particle size of 147.7±2.54μ.m. The microballoons were found to produce the percentage yield of 76.42±0.35%, drug encapsulation efficiency of 75.92±0.82 and buoyancy of 96.24±0.08% . In-vitro release showed cumulative drug release of 87.28±0.294% at the end of 12 hours and the release data found to be zero order super case II transport.